An Anisotropic Gold‐Palladium Heterostructured Nanosystem for Synergistically Overcoming Radioresistance and Enhancing Melanoma Radioimmunotherapy - Cheng Chen; Yuqi Huang; Wandong Wang; Minghao Chao; Weiguo Sun; Yinghui Kong; Guan Jiang; Yong Gao; Fenglei Gao (Advanced Science)
Abstract Radiotherapy (RT) has recently reemerged as a promising approach for melanoma treatment because of its potential to trigger abscopal effects. However, the intrinsic radioresistance of melanoma significantly diminishes RT‐induced DNA damage and the subsequent release of immunostimulatory molecules, thereby impairing systemic antitumor immunity. To overcome these challenges, a multifunctional anisotropic Au‐Pd heterostructured nanosystem (APSMR) is developed that incorporates a plasmonically enhanced Au‐Pd core, with a shell composed of a biodegradable, Mn‐doped targeting peptide. The nanosystem integrates photothermal, radiotherapeutic, and immunomodulatory functions. Under 1064 nm laser irradiation, APSMR generates reactive oxygen species (ROS) via plasmon‐driven catalysis and Mn‐mediated Fenton‐like reactions. Concurrently, mild hyperthermia (HT) promotes oxygenation and disrupts DNA repair pathways, resulting in multi‐directional DNA damage and an increase in immunogenic cell death (ICD). Furthermore, the release of Mn2⁺ ions activates the cGAS–STING pathway, which synergizes with ICD to promote systemic antitumor immunity. Notably, APSMR treatment also upregulates PD‐L1 expression, thereby sensitizing tumors to immune checkpoint blockade. Collectively, APSMR offers a potent and synergistic strategy to amplify RT‐driven tumor vaccination and improve therapeutic responses against metastatic melanoma.